2011
DOI: 10.1143/jjap.50.01ba01
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polar Anchoring Energy Based on Symmetric Oblique Incident Transmission Ellipsometry Method: the Voltage Diminution by Alignment Films

Abstract: Polar anchoring energy coefficient is one of the important parameters to improve the performance of liquid crystal displays (LCDs). To determine the polar anchoring energy coefficient with high accuracy, the symmetric oblique incident transmission ellipsometry (SOITE) method with voltage correction is proposed. As a result, the polar anchoring energy coefficients are found to be little affected by the voltage diminution at the alignment film and can be determined by the SOITE method. However, the reduced elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Many approaches with regard to the determination of polar anchoring strength were proposed. [19][20][21][22] Hung et al previously proposed a method of determining polar anchoring strength for vertical alignment based on the oblique incident transmission spectroscopic ellipsometry method. 15) In our preliminary experiments, it was confirmed that the molecular alignment of the BPLC near Mixture A is vertical (homeotropic).…”
Section: Measurement Of Polar Anchoring Strength W Dmentioning
confidence: 99%
“…Many approaches with regard to the determination of polar anchoring strength were proposed. [19][20][21][22] Hung et al previously proposed a method of determining polar anchoring strength for vertical alignment based on the oblique incident transmission spectroscopic ellipsometry method. 15) In our preliminary experiments, it was confirmed that the molecular alignment of the BPLC near Mixture A is vertical (homeotropic).…”
Section: Measurement Of Polar Anchoring Strength W Dmentioning
confidence: 99%
“…In 1998, an electro-optical measurement method for estimating 11 + 33 and/or 11 − 33 with using hybrid alignment nematic (HAN) cell under applying DC electric field has been developed [4], which has become a framework of successive research in our lab. We have also been working on establishing methods for determining device parameters such as surface anchoring energy using ellipsometer [5]. Among a series of our developed methods, the symmetric oblique incident transmission ellipsometry (SOITE) method can demonstrate its advantages also in determination of flexoelectric coefficients [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…4) Ellipsometry has been adapted not only for the determination of device parameters but also for the evaluation of surface polar anchoring energy. [5][6][7] To analyze the optical properties of LC cells, refractive indices for the ordinary and extraordinary rays are indispensable physical parameters. Generally, the refractive index of a nematic liquid crystal (NLC) is measured using an Abbe refractometer, 8,9) which has been regarded as a standard instrument.…”
Section: Introductionmentioning
confidence: 99%